Perspectivas éticas a partir de O ser e o nada em Sartre - Favero, Roberto Carlos (Universidade do Vale do Rio dos Sinos, 2015)
The objective of this thesis is to demonstrate the breadth and the derivations of the concept of freedom in Being and Nothingness of Jean-Paul Sartre (1905-1980). This is an examination designed to investigate the conditions of possibility of Sartre's concept of freedom as the foundation for an ethical-moral commitment, which expresses itself in responsibility towards the society. This approach is justified as far as the concept of freedom in Sartre is contradicted by the philosophical tradition as a concept devoid of any commitment or moral implication. Thus, the Sartrean freedom came to be as synonymous with complete or absolute freedom. To achieve the aim, we investigated the idea of freedom in Sartre. The central question guiding this study is presented in the book Being and Nothingness, in which the author constructs arguments for the phenomenological study of being or appearing to be, the conscience of that can be expected an ethical perspective. The question that guides the search is thus formulated: it is possible to deduce an ethical-moral commitment to a work whose main intention is undertake a treatise on phenomenological ontology? We demonstrate that, for Sartre, freedom is the very condition of men and if the author had intended to build a Moral Philosophy, this would be based on the attitude of engagement. In the following chapter we deal with the ethical implications of Sartre's philosophy, which become more apparent as the men realizes his limitations and, above all, his existential situation, which is marked by a state of anguish, increased by the difficulties generated in human society, in which the bad faith appears. The final chapter, where we present the main argument of the thesis identifies the idea of freedom in Sartre associated with the idea of responsibility, which is also radical in the human condition. The Sartrean existentialism is away from relativism. From Being and Nothingness is rooted in and resizes an ethic that, in absolute terms, as freedom is realized. In our conclusion, we show that the concepts freedom-responsibility in Sartre's understanding are inseparable and allows us to infer a humanistic ethics.
Keywords: Liberdade; Responsabilidade; Engajamento; Ética; Existencialismo; Freedom; Responsibility; Engagement; Ethics; Existentialism; ACCNPQ::Ciências Humanas::Filosofia